Comparing efficacy between conventional and adapted methods of automated peritoneal dialysis among patients with end stage renal disease - Suporn, Alongkot; Wongprommek, Panibud; Chunghom, Theenatchar; Tachaiya, Renoo; Anutrakulchai, Sirirat (Journal of the Nephrology Society of Thailand, 2022)
Background: Automated PD (APD) involves cycles of repeated exchanges where conventional APD (APD-C) is typically set as the same dwell time and fill volume for every cycle. Adapted APD (APD-A) is a modified new method using a short dwell time with small fill volume then subsequently using a longer dwell time and a large fill volume. A few studies conducted by the same research group have found that APD-A might improve ultrafiltration (UF) and solute clearances. Because of the limited evidence, our study aimed to compare efficacies of APD-A and APD-C methods. Methods: This study was a randomized crossover trial conducted in Srinagarind Hospital. The participants were randomly assigned by block of 4 to the APD-A or APD-C group in the first 6 weeks and then continued with the second 6-week period of crossover. The APD-A group was compared with the APD-C group on daily UF and efficacy of dialysis. Primary outcomes were weekly Kt/Vurea, weekly creatinine clearance (CrCL) and normalized CrCL (nCrCL). Secondary outcomes included UF, sodium clearance, phosphate clearance, and blood pressure control. Results: Twenty-three patients were enrolled and randomized for the first 6-week period in the APD-A group (n=13) and APD-C (n=10). The mean age was 61.1±11.8 years. Comparison between two groups showed the APD-A group had significantly higher CrCL 48.47 (36.06–76.75) vs. 46.04 (32.23–61.71) L/week (median difference 2.43 L/week, P = 0.022) and nCrCl 53.24 (45.87–72.91) vs. 49.44 (37.94–58.15) L/week/1.73m2 (median difference 3.80 L/week/1.73 m2, P = 0.02) and higher serum bicarbonate level (25.5±2.8 vs. 24.1±2.4 mEq/L, P = 0.01) and hemoglobin (10.93±1.82 vs. 10.21±1.93 g/dL, P= 0.04). No significant differences were found of other parameters and blood pressure control. No significance was observed of carry-over, period and sequence effects on treatment outcomes. Conclusion: The APD-A group had higher efficacy in CrCL, and nCrCL compared with the APD-C group. However, no demonstrated improvement was found in other clearances and UF. Generalized use of APD-A still requires more evidence from long term studies to support its benefits.